Identification of the Phosphorus-Solubilizing Bacteria Strain JP233 and Its Effects on Soil Phosphorus Leaching Loss and Crop Growth - Yu, Haiyang; Wu, Xiaoqing; Zhang, Guangzhi; Zhou, Fangyuan; Harvey, Paul R.; Wang, Leilei; Fan, Susu; Xie, Xueying; Li, Feng; Zhou, Hongzi; Zhao, Xiaoyan; Zhang, Xinjian (Frontiers in Microbiology, 2022)
Phosphorus (P) is one of the most limiting nutrients in global agricultural ecosystems, and phosphorus-solubilizing bacteria (PSB) can convert insoluble P into soluble P, thereby improving the absorption and use of soil P by plants. Increasing leaching loss of soil P due to PSB that could lead to water eutrophication is a major concern, although no direct experimental evidence is available to evaluate these effects. In this study, a highly efficient PSB strain, Pseudomonas sp. JP233, was isolated from soil and its P-solubilizing agent was identified by metabolomics and HPLC analyses. The effects of JP233 on P contents in soil leachates were also analyzed by microcosm leaching experiments in the absence and presence of maize. JP233 could solubilize insoluble P into soluble forms, and the molybdate reactive phosphorus (MRP) content reached 258.07 mg/L in NBRIP medium containing 5 g/L Ca3(PO4)2 within 48 h. Metabolomics analysis demonstrated that the organic acid involved in JP233 P solubilization was primarily 2-keto gluconic acid (2KGA). Further, HPLC analysis revealed that 2KGA contents rapidly accumulated to 19.33 mg/mL within 48 h. Microcosm leaching experiments showed that MRP and total phosphorus (TP) contents in soil leaching solutions were not significantly higher after JP233 inoculation. However, inoculation with JP233 into maize plant soils significantly decreased MRP and TP contents in the soil leaching solutions on days 14 (P < 0.01), 21 (P < 0.01), and 28 (P < 0.05). Inoculation with strain JP233 also significantly increased the biomass of maize aerial components and that of whole plants (P < 0.05). Thus, strain JP233 exhibited a significant plant-growth-promoting effect on maize development. In conclusion, the application of PSB into soils does not significantly increase P leachate loss. Rather, the application of PSB can help reduce P leachate loss, while significantly promoting plant absorption and use of soil P.